Everyday Surprise? Participants of International Exchanges Facing Culture Shock - Barbara Joanna Grabowska; Karolina Anna Kania (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
Migrations are a subject of research by specialists in various scientific disciplines. Recently, scientists have also been involved in migrations of educational background. Students, changing their country of residence for a specified time, consciously undertake tasks related to learning a new culture, language, customs or behavior. While in a culturally different country, they are subject to acculturation. This process has an individual character and course, and is associated with perceiving a culture shock. How is such a trip for intercultural exchange undertaken? What are the challenges students face? How do they overcome the encountered difficulties?